Physical And Electrical Study Of Aloe Vera Dielectric Layer - Qian, Khor Li (2013)
Commercially available Aloe vera gel and naturally extracted Aloe vera gel were compared and used as dielectric material in organic electronic device. Commercial Aloe vera and extracted natural Aloe vera layers were formed respectively on aluminum coated glass substrate by screen-printing. Both types of Aloe vera layers were dried at room temperature for 24 hours and followed by oven drying in air. The effects of oven drying temperature (30-80oC) and duration (30-60 min), number of stacking Aloe vera layers and distance in between two metal electrodes on commercial Aloe vera layer were studied. The effects of oven drying temperature (30-90oC) and duration (30-180 min) as well as loading of silicon dioxide nanoparticles (SiO2 NPs) on extracted natural Aloe vera layer were investigated. Structural, physical and electrical properties of the commercial and extracted natural Aloe vera samples were examined and compared. Atomic force microscope, scanning electron microscope, and Fourier transform infrared spectroscope were used to identify the differences between those two types of Aloe vera layers that had been dried at different conditions. It was aimed to understand the cross-linking of polysaccharides in the materials as it is an important consideration for electrical application. It found that single layer of oven dried (40°C for 30 min) commercial Aloe vera demonstrated the lowest leakage current density (J) and the J value was not affected by the distance between two metal electrodes. This revealed the electrical uniformity of the dielectric layer.